2021
DOI: 10.1155/2021/1984676
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Multiparticipant Game under a Subsidy and Punishment Mechanism: An Evolutionary Theory Perspective

Abstract: In a market with intense competition, cost pressures tempt enterprises to seek profits in ways that infringe on the interests of consumers. This is especially true when market sentiment is weak. In such situations, governments play a vital role in protecting consumers’ interests and helping struggling enterprises. We construct a tripartite game model that includes the government, enterprises, and consumers under a subsidy and punishment mechanism. We use this model to investigate the strategic choices made by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…For example, He et al [17] considered the effect of government subsidies on manufacturers' channel selection and proposed that an appropriate level of subsidies would help reduce channel competition. Based on the background of the COVID-19 epidemic, Li and Yang [18] discussed the innovation incentive effect of government subsidies on enterprises and the consumption stimulation effect on consumers. Yu et al [19] designed a model on subsidies for home appliances to the countryside and found that subsidies can help improve consumer welfare.…”
Section: Government Reward and Punishment Mechanismmentioning
confidence: 99%
“…For example, He et al [17] considered the effect of government subsidies on manufacturers' channel selection and proposed that an appropriate level of subsidies would help reduce channel competition. Based on the background of the COVID-19 epidemic, Li and Yang [18] discussed the innovation incentive effect of government subsidies on enterprises and the consumption stimulation effect on consumers. Yu et al [19] designed a model on subsidies for home appliances to the countryside and found that subsidies can help improve consumer welfare.…”
Section: Government Reward and Punishment Mechanismmentioning
confidence: 99%